206 A randomized trial testing remuneration protocols to maximize concussion patient retention for real-time symptom and activity monitoring. (5th May 2020) - Orchinik, Julia; Corwin, Daniel; Master, Christina; Delgado, Mucio (Kit); Patel, Mitesh; Wiebe, Douglas
Abstract : Statement of Purpose: We are honing the ReCoUPS (Recovering Concussion Update on the Progression of Symptoms) protocol to monitor concussion patients using ecologic momentary assessment (EMA), and accrue data revealing the relationship between physical and cognitive rest and clinical outcomes in the days and weeks post-injury. Methods/Approach: Our randomized trial uses behavioral economics to identify a remuneration strategy that enhances retention. Staff at one pediatric and one adult ED enroll concussion patients using the ReCoUPS platform, that assigns participants to one of four treatment arms that dictate the remuneration scheme. Participants receive a Fitbit, download the ReCoUPS app onto their smartphone, receive 3 prompts daily, and respond over 3 weeks. The EMA data collected include concussion symptoms and cognitive rest/activity (self-reported time reading, time at work/school) reported at each prompt, screen time, and step count (Fitbit). The maximum possible remuneration for three arms is $300 for adults (age 18–64 years) and $50 for children and adolescents (13–17 years), whereas in one arm only a Fitbit is given to keep. Results: Fifteen participants were enrolled in the EDs. The proportion of responses completed was 87% in the loss-based arm and 86% in the streak accrual arm, compared to 47% where the FitBit was given as remuneration, and 46% in the control arm where the maximum given regardless of number of responses completed. Enrollment will continue to 20 in each arm to determine whether these differences remain. Conclusions: Loss-based and streak remuneration were equally effective to prevent study attrition in this longitudinal follow-up study, whereas the Fitbit remuneration and flat-fee control were not effective. Significance and Contributions to Injury and Violence Prevention Science: Remuneration plays a key role in retention and can help accomplish the longterm follow-up required to obtain data on concussion recovery.